PENILAIAN KINERJA PERBANKAN NASIONAL DENGAN MODEL DISKRIMINAN LINIER - Haryo Satriyawan (Fakultas Bisnis UKDW, 2005)
Indoqesian eeonomic condition is still unstable. Thi* emerges a very high riskfor bonking to get truubles in ix financial. The national banking which should futtction as the pesent ntles, in the practice, theru are sofrre urrwantes things happen- This unhealthy practice will couse the crisrs in the ndional ban*ing. Finally, this witt c(ruse a decrcase in the health of national banking * , onit